Le medie imprese di fronte alla crisi: il caso Meccanotecnica Umbra S.p.A. - Ceccacci, Francesca; Devetag, Giovanna (Piccola Impresa / Small Business, 2014)
Scope of the present work is to analyze how Meccanotecnica Umbra S.p.A. has attempted to cope with the current global economic crisis. Meccanotecnica Umbra S.p.A. is a world renowned producer of mechanical seals, covering 35% of the world automotive industry and 65% of the European household appliance market. In 2010, Meccanotecnica ranked first among the most dynamic senior companies according to Mediobanca. Since 2000, the Group has pursued an intense internationalization and diversification strategy, entering the chemical, pharmaceutical, paper and food industries. It is currently present in every continent, owning both distribution channels and production plants. Meccanotecnica has paid particular attention to technological innovation, through which it has achieved complete automation and control in the production process. Furthermore, investments in plant and product innovation, combined with strong embeddedness in the local community, have also contributed to its positive results notwithstanding the economic crisis. The present study has adopted a qualitative approach based on a field case study. Diverse and complementary data gathering